Synthesis, and prediction of molecular properties and antimicrobial activity of some acylhydrazones derived from N-(arylsulfonyl)methionine - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY; ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2016)
A series of 38 new acylhydrazones [3-40], derived from (2S)-4-(methylsulfanyl)-2-[[(4-methylphenyl)sulfonyl] amino]butanoic acid hydrazide [2], were synthesized and evaluated for their anti-HIV and antimicrobial activity with the further aim to develop acylhydrazones carrying an amino acid side chain. All tested compounds possess stronger activity against gram (+) bacteria. Compound 23 was found active against methicillin-resistant Staphylococcus aureus (MRSA) with a MIC value of 3.9 mu g/mL. The MIC value of compound 30 against Enterococcus faecalis, Listeria monocytogenes, and Bacillus cereus was 8 mu g/mL. A computational study for prediction of ADME and drug-like properties (solubility, drug-likeness, and drug score) as well as potential toxicity profiles of compounds 2-40 was performed using the Molinspiration online property calculation toolkit and Osiris Property Explorer. As most of our compounds meet Lipinski's rule of five, they promise good solubility and permeability. According to Osiris calculations, the majority of our compounds are supposed to be nonmutagenic and nonirritating.
Keywords: Acylhydrazones; antimicrobial activity; L-methionine; microwave-assisted synthesis; MRSA; HIV-1 REVERSE-TRANSCRIPTASE; PROTEIN SYNTHASE III; RIBONUCLEASE-H; HYDRAZIDE DERIVATIVES; BIOLOGICAL-ACTIVITIES; ANTIVIRAL EVALUATION; ANTIFUNGAL ACTIVITY; COLORIMETRIC ASSAY; N-ACYLHYDRAZONES; ANTI-HIV